HYDROGEOCHEMICAL STUDY OF SPRINGS AROUND THE PATUHA GEOTHERMAL FIELD - Imanuddin Prakasa, Fakhmi
Indonesia is a country traversed by the world's volcanic arc and surrounded by active tectonic setting. Indonesia has a large potential for geothermal resources, West Java is no exception. The presence of geothermal reservoirs below the surface is reflected on the surface through the emergence of geothermal manifestations, such as hot springs. The existence of geothermal manifestations on the surface occurs due to the propagation of heat from below the surface through the permeable zone. In geothermal exploration, temperature, water/steam ratio, chemical evolution, and geothermal fluid flow systems are important factors of the reservoir for evaluating its potential of geothermal resources. The study of the hydrogeochemical pattern of geothermal fluids can be used to understand the type of water that arises from geothermal manifestations to predict the geothermal system which will later help further research on the existing geothermal potential. By researching fluids from springs or manifestations that appear, it is hoped that it can clarify the origin, water-rock interactions, and the chemical evolution of geothermal fluids along with the flow from the reservoir to the surface through the manifestations around the Patuha Geothermal Field. Several analyzes can be carried out in hydrogeochemical studies, such as analysis of the physicochemical properties of water, analysis of principal ions using Piper Diagrams and Ternary Diagrams, and analysis of the isotope ratios of water ? 18O and ? 2H. The research suspects that there are four types of water around the Patuha Geothermal Field, namely sulfate water, sulfate-chloride water, sulfate-bicarbonate water, and bicarbonate water. Based on the results of ? 18O and ?2H isotopes, water sources from water samples at the Patuha Geothermal Field show that most of the samples are potentially mixing with meteoric water and other minor sources, such as H2S exchange, and reactions with minerals.